Follow-up interval for dental appointments: a randomized clinical trial with children with low caries risk - BERTI,Gabriela Oliveira (2021)
Abstract The objective of this study was to evaluate the effect of different follow-up consultation intervals on caries incidence in children with low caries risk. The study was composed of 224 children aged between 3 and 5 years and with low risk of caries. The children were randomly allocated into two groups, according to two different follow-up consultation intervals: Group 1 (G1) – 12-month follow-up interval; Group 2 (G2) – 18-month follow-up interval. All oral clinical examinations were performed by a single examiner who was previously calibrated and blinded in relation to the study groups. An external dentist provided the advice on oral hygiene and diet and evaluated the children’s socioeconomic conditions. The Chi-square and Mann-Whitney tests were used to evaluate the differences between groups. Poisson regression analyses were performed to assess the association of caries incidence with the other variables. At the end of the study there was a significant difference between the groups regarding initial active lesions (p = 0.012), and children in G2 were at a higher risk of developing initial active lesions than those in G1 (p = 0.047). Children who had a higher number of teeth with initial active lesions in the follow-up consultations were at a higher risk of developing cavitated dentin caries (p = 0.001). Both follow-up intervals are justifiable. Although significant results have been observed for initial active caries lesions within the 18-month follow-up interval, it should be noted that these lesions can be treated using just preventive measures. Besides, different return interval had no effect in cavitated dentin lesions.